Methodological framework to apply a financial risk management model within the UNED - Arce Solano , Jorge Luis (2019)
This paper offers a technical frame of reference in order to make a model for managing financial riskin a university.These are the results of are search carried out in 2013. Theoretical aspects of risk management are analyzed; it also shows the AS/NZS 4360:1999, Australian Standard of Risk Management, which brings a series of definitions in order to understand the way it is applied in organizations. Methodology has a  central  objective and  three  specific ones that show the route to  follow  in order  to  make the management  model. Some elements  were analyzed such asthe characteristics for  business risk management and in doing so, the actions to determine probabilities were taken into account (risk level of occurrence) and impacts (consequences that may generate risk), techniques and alternatives to mitigate risk and finally how to follow them upduring the whole process of risk management. From there on the model to implement proposed.